Understanding the lived experiences of healthcare professionals during the COVID-19 pandemic: an interpretative phenomenological analysis. Issue 1 (1st January 2021) - McGlinchey, Emily; Hitch, Catherine; Butter, Sarah; McCaughey, Laura; Berry, Emma; Armour, Cherie
ABSTRACT: Background : Little research has examined the impact of working within the context of COVID-19 on UK healthcare professionals (HCPs) mental health and well-being, despite previous pandemic findings indicating that HCPs are particularly vulnerable to suffering PTSD and other mental health difficulties due to the nature of healthcare work. Specifically, it appears that no research has employed qualitative methodologies to explore the effects of working amidst COVID-19 on mental health for HCPs in the UK. Objective : To qualitatively examining the lived experiences of HCPs in Northern Ireland, working during the early stages of the pandemic and lockdown period (14.04.20 and 29.04.20). Method : Interpretative phenomenological analysis (IPA) was used to explore the experiences of healthcare professionals, who were working during the COVID-19 outbreak. Ten HCPs were recruited via a social media campaign and snowball sampling. All interviews were conducted via telephone and transcribed verbatim. Results : Three superordinate themes with subordinate themes were elicited through the analysis. Theme one centred on specific challenges of HCPs working during the pandemic, such as redeployment, isolation from loved ones, infection concerns, lack of PPE and impact on patient interpersonal care. Theme two offered insights into the mental health and wellbeing of HCPs, while many experienced feelings of fear, sadness and hypervigilance, all also demonstrated a marked resilience. Finally, many felt undervalued and misunderstood, and wished to press upon the general public seriousness of the disease. Conclusion : To the authors' knowledge this is the first study to explore in depth, the unique experiences of frontline HCPs in Northern Ireland, offering a detailed account of the challenges confronted in these unprecedented circumstances and highlighting support needs within this cohort. HIGHLIGHTS: The current study qualitatively examines the experiences of frontline healthcare professionals working during the early stages of the COVID-19 pandemic in the UK. Three superordinate themes with subordinate themes emerged from the analysis, broadly covering key areas such as navigating new occupational challenges, maintaining mental health and wellbeing under precedented circumstances, and managing feelings being misunderstood and undervalued. Specific challenges included sudden redeployment, resulting often in a change in job role (and/or location) as well as a loss of important work related social networks because of this, isolation from loved ones, infection concerns, lack of (or limited supply of) personal protection equipment and impact on patient interpersonal care. The findings suggest that being a healthcare professional during this time does not come without personal cost and has the potential to put pressure on one's psychological state, with many participants experienced feelings of fear, sadness and hypervigilance, as well as physical exhaustion. All participants demonstrated a marked resilience in their ability to continue to do navigate their work environment and were able to employ adaptive coping strategies however, some expressed concern that this is waning. It is essential that we do not neglect a workforce which is working tirelessly at great personal cost to keep each one of us safe and support the continued wellbeing and resilience of healthcare professionals. It is argued that in order to adequately support healthcare professionals physical and mental health we must tackle this on three main fronts, at a Government level, a research and intervention level and at a societal level.